USING HIGH TECHNOLOGIES TEACHING FOREIGN LANGUAGES TO THE STUDENTS: USING HIGH TECHNOLOGIES TEACHING FOREIGN LANGUAGES TO THE STUDENTS - Rahmonova, Hadicha (Журнал иностранных языков и лингвистики, 2022)
Abstract: This paper aims to highlight the role of using modern technology in teaching English as a second language. It discusses different approaches and techniques which can assist English language students to improve their learning skills by using technology.